CD73 Expression on Mesenchymal Stem Cells Dictates the Reparative Properties via Its Anti-Inflammatory Activity. (2nd May 2019) - Tan, Kezhe; Zhu, Hongtao; Zhang, Jianfang; Ouyang, Weili; Tang, Jianfeng; Zhang, Youming; Qiu, Linlin; Liu, Xueqing; Ding, Zhaoping; Deng, Xiaoming
Abstract : Mesenchymal stem cells (MSC) are not universal and may be subject to dynamic changes upon local milieus in vivo and after isolation and cultivation in vitro. Here, we demonstrate that MSC derived from murine pericardial adipose tissue (pMSC) constitute two cohorts of population distinguished by the level of CD73 expression (termed as CD73 high and CD73 low pMSC). Transplantation of two types of cells into mouse hearts after myocardial infarction (MI) revealed that the CD73 high pMSC preferentially brought about structural and functional repair in comparison to the PBS control and CD73 low pMSC. Furthermore, the CD73 high pMSC displayed a pronounced anti-inflammatory activity by attenuating CCR2 + macrophage infiltration and upregulating several anti-inflammatory genes 5 days after in vivo transplantation and ex vivo cocultivation with peritoneal macrophages. The immunomodulatory effect was not seen in cocultivation experiments with pMSC derived from CD73 knockout mice (CD73 -/- ) but was partially blocked by pretreatment of the A2b receptor antagonist, PSB603. The results highlight a heterogeneity of the CD73 expression that may be related to its catalytic products on the modulation of the local immune response and thus provide a possible explanation to the inconsistency of the regenerative results when different sources of donor cells were used in stem cell-based therapy.